2016
DOI: 10.3389/fmicb.2016.01450
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Xylanase Production through Response Surface Methodology by Fusarium sp. BVKT R2 Isolated from Forest Soil and Its Application in Saccharification

Abstract: Xylanses are hydrolytic enzymes with wide applications in several industries like biofuels, paper and pulp, deinking, food, and feed. The present study was aimed at hitting at high yield xylanase producing fungi from natural resources. Two highest xylanase producing fungal isolates—Q12 and L1 were picked from collection of 450 fungal cultures for the utilization of xylan. These fungal isolates—Q12 and L1 were identified basing on ITS gene sequencing analysis as Fusarium sp. BVKT R2 (KT119615) and Fusarium stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Apart from biorefinery, xylanases have a potential industrial application in various fields like wine making, textile, paper and pulp industries, animal husbandry, bread making, fruit juice extraction [7] etc. Production of xylanases in large scale is gaining much importance in getting the scope to cut down the enzyme cost with the use of high yielding microbes [8]. Xylanase production by various organisms have been studied like fungi [7], bacteria [9], yeast, [10], and even with co-culture of more than one organism [11].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from biorefinery, xylanases have a potential industrial application in various fields like wine making, textile, paper and pulp industries, animal husbandry, bread making, fruit juice extraction [7] etc. Production of xylanases in large scale is gaining much importance in getting the scope to cut down the enzyme cost with the use of high yielding microbes [8]. Xylanase production by various organisms have been studied like fungi [7], bacteria [9], yeast, [10], and even with co-culture of more than one organism [11].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from biorefinery, xylanases have a potential industrial application in various fields like wine making, textile, paper and pulp industries, animal husbandry, bread making, fruit juice extraction (Chadha et al, 2019) etc. Production of xylanases in large scale is gaining much importance in getting the scope to cut down the enzyme cost with the use of high yielding microbes (Ramanjaneyulu and Rajasekhar Reddy, 2016). Xylanase production by various organisms have been studied like fungi (Chadha et al, 2019), bacteria (Kumar et al, 2018), yeast, (Ergun and Çalık, 2016), and even with co-culture of more than one organism (Yardimci and Cekmecelioglu, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…RSM method by Azzouz et al [ 39 ] reported a 65.01% increase in xylanase output by Aspergillus niger strain BG on 84% humidified wheat bran with a pH of 2.5 at 37°C and incubation for 66 h. Statistical analysis of xylanase output by Aspergillus foetidus in submerged fermentation with soybean scraps revealed that variables pH and the interaction of pH and temperature influenced xylanase biosynthesis, with good xylanase activity (13.98 U/mL) at pH 7.0, 28 °C, and 120 rpm for 168 hours [ 40 ]. Response surface methodology by Ramanjaneyulu and Rajasekhar [ 41 ] for maximal production of xylanase (4560 U/mL) by Fusarium sp. BVKT R2 demonstrated that the optimal conditions were sorbitol 1.5%, yeast extract 1.5%, pH of 5.0, temperature of 32.5 °C, and shaking of 175 rpm.…”
Section: Discussionmentioning
confidence: 99%